Physico-Chemical and Microbiological Analysis of Under Ground Water in V.V Nagar and Near by Places of Anand District,Gujarat, India - Arunabh Mishra; Vasishta Bhatt (E-Journal of Chemistry)
A report of physico-chemical and microbial study of the water samples taken from the region nearby Anand district of central Gujarat is presented here. Six water samples are subjected to physico- chemical analysis like pH, TDS, hardness, conductivity, dissolved oxygen and chemical oxygen demand. The MPN count resulted from the bacteriological study of these samples has given the information regarding the suitability of the water for drinking and other domestic applications. The results are analyzed comparatively and conclusions regarding the suitability of the use of such waters are made.